Kelalaian Penyelenggara Yang Mengakibatkan Kecelakaan Dalam Road Race (Balap Motor) Di Kota Atambua Kabupaten Belu - Alexandro Mario Louise Saka Besi; Deddy R. CH. Manafe; Adrianus Djara Dima (Artemis Law Journal, 2026)
This research investigates the negligence of organizers that resulted in accidents during road race (motorcycle racing) events in Atambua City, Belu Regency. The study was prompted by a fatal incident during a practice session, where inadequate technical inspection led a participant to lose control and crash into spectators, causing severe injuries and one fatality. The aim is to examine the forms of negligence committed by organizers and their legal implications. Employing a socio-legal research method with an empirical juridical approach, data were collected through interviews and direct observation at the incident site. The findings reveal that the negligence included poor supervision of vehicle conditions, non-compliance with safety standards, and weak coordination—actions considered to violate legal norms. Legal enforcement involves investigation, administrative sanctions by regulatory bodies such as the Indonesian Motor Association (IMI), and the potential for criminal liability under Article 359 of the Indonesian Criminal Code (KUHP), which addresses negligence causing death or serious injury.